What is trauma? Qualitatively assessing stakeholder perceptions in Santa Cruz de la Sierra, Bolivia. Issue 9 (1st September 2020) - Blair, Kevin J.; Monroy, Alexa; Rook, Jordan M.; Wood, Ethan; Foianini, J. Esteban; Haider, Adil H.; Swaroop, Mamta; Boeck, Marissa A.
ABSTRACT: Addressing the burden of injury in low-resource settings requires development of trauma systems. This study aimed to describe perceptions of trauma in Santa Cruz, Bolivia to better inform strategies for trauma system development. In 2015–2016, we conducted 16 individual and 11 group interviews with key stakeholders involved with or exposed to trauma. A pile sorting activity showed participants pictures of injury mechanisms to explore perceptions of trauma. Responses were analysed for themes using content and discourse analysis. Among 27 interviews, six were with physicians, seven with first responders, three with community members, and 11 with trauma patients. Pictures commonly categorised as trauma depicted a road traffic incident (92.6%), fall (88.9%), gunshot wound (88.9%), and burn (85.2%). Fewer respondents stated intoxication (51.9%) or drowning (40.7%) were trauma. Coding of responses revealed five themes: trauma definition, mechanism, physical injury, management, and psychological trauma. Medical personnel focused more on trauma as mechanism, physical injury, and management, whereas laypersons commonly described trauma as psychological. Varied understanding of what represents trauma could influence trauma registry data collection. Laypersons' focus on psychological trauma may affect use of designated trauma care hospitals. These viewpoints must be considered when designing policies and interventions for trauma system strengthening.